Physiological and environmental effects on first calving age in milking crossbred cows of the production system at the CNPGL/Embrapa - Filho, Geraldo Noronha Junqueira; Verneque, Rui da Silva; Lemos, Álvaro de Matos; da Silva, Hamilton Carmélio Machado; Reis, Ronaldo Braga (Pesquisa Agropecuaria Brasileira, 1992)
This study was conducted with the data from crossbred Holstein-Zebu-Gir (H-Z) cows in the Production System which was introduced in 1977 at the CNPGL/EMBRAPA, Coronel Pacheco, MG, Brazil. The effects of physiological and environmental factors on the age of the first calving were studied. General mean and standard deviation of 131 heifers were 40.7 ± 0.4 months. The new system improved the first calving age (P < 0.01) which was 47.2 months (from 46 cows) to 34.1 for the other 85 cows raised within the System. The year effect within Systems affected (P < 0.01) that characteristic; the animals born in years before this System has been introduced, presented greater variation than that of the animals born after 1977. Birth season also influenced (P < 0.05) the age at the first calving, as well as the genetic groups within the System (P < 0.01). The 1/2, 3/4 and 7/8 heifers had all equivalent first calving age. Prior to the System the half blood bred had earlier first calving age than the 3/4 H-Z bred. Birth season and System interacted as expected on the above characteristic (P < 0.05).